POLITIC OF ISLAMIC DEVELOPMENT IN THE CITY OF HANOI (VIETNAM): STUDY OF HALAL FOOD RESTAURANT - Warjio Warjio; Heri Kusmanto (Universitas Medan Area, 2015)
For Muslims, halal food is important. This is not only of the demands of sharia but also related to the issue of identity. Wherever they are, halal food can not be separated from them, except in emergency circumstances. Included in this when they are in a country where people are not Muslims. Hanoi City, is one of the cities in the country of Vietnam that majority of the people are Buddhist. As a city that is building itself and become one of the tourist destination, Hanoi is visited by many tourists, including Muslim tourists. For Muslim travelers, the main problems encountered when in Hanoi is halal food. To meet the demands of these Muslim travelers, a few restaurants in the city of Hanoi providing halal food. Enterprises providing halal food is done by the employer Muslim or not. The results of my research, several restaurants, found several problems associated with this halal food. This paper will explain how the exploratory effort to develop halal food in the city of Hanoi. Who are involved in the effort to develop the halal food? What are the problems faced in the effort to build the halal food?